Immune Reconstitution Inflammatory Syndrome: Opening Pandora’s Box - Mariana Meireles; Conceição Souto Moura; Margarida França (Case Reports in Infectious Diseases)
One of the purposes of antiretroviral therapy (ART) is to restore the immune system. However, it can sometimes lead to an aberrant inflammatory response and paradoxical clinical worsening known as the immune reconstitution inflammatory syndrome (IRIS). We describe a 23-year-old male, HIV1 infected with a rapid progression phenotype, who started ART with TCD4+ of 53 cells/mm3 (3,3%) and HIV RNA = 890000 copies/mL (6 log). Four weeks later he was admitted to the intensive care unit with severe sepsis. The diagnostic pathway identified progressive multifocal leukoencephalopathy, digestive Kaposi sarcoma, and P. aeruginosa bacteraemia. Five weeks after starting ART, TCD4+ cell count was 259 cells/mm3 (15%) and HIV RNA = 3500 copies/mL (4 log). He developed respiratory failure and progressed to septic shock and death. Those complications might justify the outcome but its autopsy opened Pandora’s box: cerebral and cardiac toxoplasmosis was identified, as well as hemophagocytic syndrome, systemic candidiasis, and Mycobacterium avium complex infection. IRIS remains a concern and eventually a barrier to ART. Male gender, young age, low TCD4 cell count, and high viral load are risk factors. The high prevalence of subclinical opportunistic diseases highlights the need for new strategies to reduce IRIS incidence.